1998
DOI: 10.1021/jo9803129
|View full text |Cite
|
Sign up to set email alerts
|

Direct Approach to α-Hydroxyphosphonic and α,ω-Dihydroxyalkane-α,ω-bisphosphonic Acids by the Reduction of (Bis)acylphosphonic Acids

Abstract: Acylphosphonic and bisacylphosphonic acid sodium salts were directly reduced by sodium borohydride to the corresponding hydroxyphosphonates and dihydroxyalkanebisphosphonates. The solution conformation of the (bis)hydroxyphosphonic acid sodium salts, elucidated from the homonuclear and heteronuclear coupling constants of the proton adjacent to the hydroxy and the phosphonic groups, was identical with the solid-state conformation as determined for 1-hydroxy-2-phenylethylphosphonic acid, a representative compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…12 The MAS spectrum of 5 [see Fig. 3(c)] shows two sideband systems with an integral intensity ratio of 1 : 1.4.…”
Section: Mas Nmr Investigation Of Bisphosphonatesmentioning
confidence: 99%
“…12 The MAS spectrum of 5 [see Fig. 3(c)] shows two sideband systems with an integral intensity ratio of 1 : 1.4.…”
Section: Mas Nmr Investigation Of Bisphosphonatesmentioning
confidence: 99%
“…HRMS: calcd for C 7 H 10 O 4 P 189.0317 (M+H) + . Found 189.0320.The spectroscopic data were in agreement with the values described in the literature 24. The free acid was then reacted with cyclohexylamine in EtOH, following the literature procedure, to afford the dicyclohexylammonium salt as a white solid 22.…”
mentioning
confidence: 68%
“…We have recently described this reaction, along with the structures of the resulting dihydroxybisphosphonates [24]. …”
Section: Synthesesmentioning
confidence: 99%
“…Therefore, we synthesized a series of ␣,xdihydroxypolymethylene-␣,x-bisphosphonic acids (12, 13, 14) [24]. It was found that compounds 12 and 13, corresponding in lengths to AdBP and PiBP, respectively, are inactive at low concentrations (0.1 mM) in vitro.…”
Section: Figurementioning
confidence: 99%